2011
DOI: 10.1021/pr200147g
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Metabolic Transformation in Tumor Invasion and Metastasis in Mice with LM-8 Osteosarcoma Cell Transplantation

Abstract: While extensive evidence indicates that tumor cells shift their global metabolic programs, the molecular details of the metabolic transformation in tumor invasion, progression, and metastasis remain largely unknown. Characterization of the time-dependent metabolic shift during the tumor invasion, development, and metastasis will describe an important aspect of tumor phenotypes and potentially allow us to design therapies that inhibit tumor cell movement. In this study, a metabonomic study was performed to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…Additionally, in accordance to our study, increase in lipid metabolism over the metabolism of carbohydrates and amino acids was associated with tumor metastasis6. The increased metastatic potential of tumor cells associated with AA can be directly linked with its derivatives namely eicosanoids (prostaglandins, leucotrines, hydroxyeicosatraenoic acids), promoting angiogenesis, and subsequently metastatic spread38.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, in accordance to our study, increase in lipid metabolism over the metabolism of carbohydrates and amino acids was associated with tumor metastasis6. The increased metastatic potential of tumor cells associated with AA can be directly linked with its derivatives namely eicosanoids (prostaglandins, leucotrines, hydroxyeicosatraenoic acids), promoting angiogenesis, and subsequently metastatic spread38.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, modulatory effect of tumor microenvironment on cancer cell metabolism was reported5, as well as metabolic alterations associated with metastasis6, which suggests tight regulation of tumor invasiveness by the microenvironment via metabolic - oncogenic signaling crosstalk’s. The abnormal glycolitic activity assocaited with lactate production, was recognized as specific characteristics of cancer metabolism by Otto Warburg in the late 1920s7.…”
mentioning
confidence: 99%
“…Results demonstrate that pancreatic b-cells undergo apoptosis in response to camptothecin or staurosporine, but not pro-inflammatory cytokines. A study was performed to characterize the global metabolic changes during the process of tumor invasion and metastasis to murine osteosarcoma cell (Hua et al, 2011). Serum metabolic profiling revealed that many key metabolites in glycolysis and tricarboxylic acid (TCA) cycle, as well as most of the amino acids were elevated at rapidly growing stages of tumor, presumably resulting from a high energy demand and turnover of anabolic metabolism during the tumor cell proliferation.…”
Section: Cancer Cellsmentioning
confidence: 99%
“…7 This technology has been extensively used to identify metabolite-based biomarkers in various cancers. 812 Differentially expressed serum or plasma metabolites have been reported, involving intermediates in glycolysis, TCA cycle, urea cycle, arginine and proline metabolism, fatty acid metabolism, and gut flora metabolism associated with CRC morbidity. 13,14 However, cancer metabonomics studies 1520 often generate different metabolite markers due to the different clinical protocols used and the wide dynamic range of metabolites measured by different platforms.…”
Section: Introductionmentioning
confidence: 99%